The power development project = (The World Bank in Vietnam (WB), 2003)
The main objectives of the Power Development Project are to: 1) help meet the rapid growth in electricity demand in the South of Viet Nam through the addition of new gas-fired generating capacity; 2) strengthen the high voltage (HV) transformation capacity in Viet Nam; 3) assist the government in the introduction of private power in the country; 4) strengthen the institutional capacity of Electricity of Viet Nam (EVN) through technical assistance and training; and 5) assist in the formulation of a national strategy and master plan for rural electrification. The project will finance the following components: 1) installation of 2x150 megawatt (MW) gas turbines for the first 450 MW Combined Cycle (CC) power block of the Phu My power station; 2) addition of about 900 megavolt-amperes (MVA) of such capacity in other parts of the country; 3) resettlement and compensation of persons affected by the Phu My plant; and 4) consulting services for: (a) project design and supervision for Phu My; (b) development of a Build-Operate-Transfer (BOT) type of arrangement for the second CC power block of Phu My on the basis of competitive bidding; (c) technical assistance and training for EVN managerial staff; (d) master plan for rural electrification; and (e) technical studies for the Dai Ninh hydropower project.